THE ROLE OF NATIONAL WITCHCRAFT HERITAGE IN THE SPIRITUAL RISE OF SOCIETY (SOCIO-PHILOSOPHICAL ANALYSIS) - Muydinov Asilbek Adham o’g’li (Journals Park Publishing, 2022)
Society is a special form of the Association of people, the sum of a huge number of relations that are valid between people; part of nature; Social being. Society is an extremely complex and multifaceted phenomenon, which has a constant nature of change and development. Since very ancient times, the great thinkers of mankind have tried to know the essence of society and determine the role and role of man in society. In different historical periods, mythological, religious, scientific and philosophical views made it possible to form certain knowledge, perceptions of the origin and development of society.
Keywords: origin and development of society, sophisticated and reliable scientific and philosophical